An outbreak of toxoplasmosis in squirrel monkeys (Saimiri sciureus) in South Korea. Issue 4 (30th April 2018) - Oh, Hanseul; Eo, Kyung‐Yeon; Gumber, Sanjeev; Hong, Jung Joo; Kim, C‐Yoon; Lee, Hyun‐Ho; Jung, Young‐Mok; Kim, Jin; Whang, Gyu‐Whan; Lee, Ji‐Min; Yeo, Yong‐Gu; Ryu, Bokyeong; et al.
Abstract: Background: Toxoplasma gondii ( T. gondii ) is an intracellular protozoan parasite that can infect warm‐blooded animals including humans. New World monkeys, such as squirrel monkeys, are more susceptible to T. gondii than Old World monkeys, often developing fatal disease. Methods: In this study, seven of thirteen dead squirrel monkeys at Seoul Grand Park were tested to find the cause of sudden death. Results: The main histopathological findings included interstitial pneumonia, necrotizing hepatitis, and splenitis. Periodic acid‐Schiff staining of liver, spleen, and lung revealed cyst structures consistent with bradyzoites. Amplification of the B1 gene was detected in the liver or spleen of all monkeys. Additionally, a restriction fragment length polymorphism assay and phylogenetic analysis of the GRA6 amplicon revealed a consistent clustering with the type II strain of T. gondii . Conclusions: This study is the first report of T. gondii infection of squirrel monkeys in Korea, and the first report of type II T. gondii based on GRA6 analysis in Korea.